The Role of Work Engagement as Mediator in Improving Organizational Performance in Manufacturing Companies - Setyawan, Agustinus; Yuswardi, Yuswardi; Jerry, Jerry (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
This study investigates the role of work engagement as a mediator in enhancing organizational performance, particularly within the manufacturing industry. Employing a quantitative research design, the researchers collected data through structured questionnaires distributed to employees across four leading manufacturing companies in Batam, Indonesia. The sample size comprised 300 valid respondents, determined based on the total questionnaire items multiplied by ten, aligning with established sampling formulas. To analyze the hypothesized relationships, the study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM), following the procedural guidelines of Ghozali (2021) and Hair et al. (2019). The data underwent rigorous testing, including assessments of reliability, validity, and multicollinearity, before conducting hypothesis testing. The results confirmed that work engagement significantly mediates the effects of organizational innovation and talent management on organizational performance, with all mediation effects supported by high T-values (>1.96). Meanwhile, the influence of HR practices and knowledge management on performance through work engagement showed mixed results. Based on these findings, the research recommends that organizations formulate effective strategies to foster work engagement, thereby improving overall performance. The study contributes to the theoretical understanding of the mediating role of work engagement and offers practical insights for organizational leaders.